PENGARUH SUMBER INFORMASI TERHADAP TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI PADA REMAJA DI WILAYAH PESISIR KALIMANTAN UTARA - Nur Indah Noviyati (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2023)
Improving the quality of youth begins with paying attention to reproductive health. Adolescent problems related to reproductive health are child marriages, the number of which increases every year in North Kalimantan. There are several studies showing that there are several factors that can cause differences in knowledge among adolescent students. This study aims to determine the level of knowledge of reproductive health in adolescents in the coastal area of ​​North Kalimantan. This research is a descriptive research, with the research variable being knowledge of adolescent reproductive health in the coastal city of Tarakan (Charity Beach). The population of this study amounted to 100 people. The criteria in this study are; adolescents moving up the middle and high school ladders. In taking the sample is done by using purposive sampling. For young women to know about reproductive health, by providing good information from the school as many as 7 young women (23.3%), then information from parents with a good level of knowledge as many as 6 young women. teenagers (20%), while for information from social media there are only 3 children who have good knowledge (10%). Knowledge about reproductive health in adolescents through parents, schools and social media. When parents, schools and social media are actively involved in providing accurate, supportive and comprehensive information, young women can obtain better knowledge.